2007
DOI: 10.1889/1.2709738
|View full text |Cite
|
Sign up to set email alerts
|

Highly conductive SnO2 thin films for flat‐panel displays

Abstract: Abstract— SnO2 is considered to be a promising alternative material for indium tin oxide (ITO), which is used for thin‐film transparent electrodes in flat‐panel displays (FPDs) and is facing a serious indium depletion problem. However, annealing processes in the manufacture of plasma‐display panels (PDPs), which are major FPDs, cause high resistivity in SnO2 films. To obtain lower resistivity after the annealing processes, the relationship between deposition conditions and resistivity and the influences of ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
27
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…The ability to verify final product, indicate and establish the contaminants, and observe the integrity of surfaces is crucial to correlating performance characteristics with composition. Semiconductor thin films have recently received a great scientific interest because of its wide range of applications like gas sensors [1], dye-sensitized solar cells [2], ion-sensitive field effect transistors [3], catalysts [4], and transparent electrodes for flat panel displays [5]. Semiconducting tin oxide SnO 2 is also widely used in optoelectronic devices, s, photoelectron chemical devices, and solar photovoltaic (PV) cells where it was observed that composition and defects strongly influence the performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to verify final product, indicate and establish the contaminants, and observe the integrity of surfaces is crucial to correlating performance characteristics with composition. Semiconductor thin films have recently received a great scientific interest because of its wide range of applications like gas sensors [1], dye-sensitized solar cells [2], ion-sensitive field effect transistors [3], catalysts [4], and transparent electrodes for flat panel displays [5]. Semiconducting tin oxide SnO 2 is also widely used in optoelectronic devices, s, photoelectron chemical devices, and solar photovoltaic (PV) cells where it was observed that composition and defects strongly influence the performance [6].…”
Section: Introductionmentioning
confidence: 99%
“…Because the one-dimensional SnO 2 nano-material has special gas-sensing, light transmittance and electric conduction characteristics, 1 it becomes an ideal material candidate swiftly for gas sensors, 2-4 transparent electrodes, 5 6 light emitter diode, 7 flat-panel display 8 and thin film solar cell 9 etc. Furthermore, after it is doped by some impurities, SnO 2 nano-material has more extensive use because of the emergence of some better performances.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, we studied Cr/SnO 2 [3][4][5] as a protective layer. In this case, Cr is an adhesive layer.…”
Section: Introductionmentioning
confidence: 99%